2016
DOI: 10.4236/jdm.2016.64024
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Periodontal Diseases: An Established Two-Way Relationship

Abstract: Background: Periodontal diseases (PD), including periodontitis, are chronic inflammatory pathologies caused by bacteria in the subgingival biofilm which affect the periodontal tissues. PD is now considered a localized, chronic, oral infection that activates the host immuno-inflammatory responses both locally and systemically, and also constitutes a source of bacteraemia. It is a known fact that periodontal diseases exercise an important influence on the pathogenesis of numerous systemic diseases, including dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 80 publications
0
6
0
2
Order By: Relevance
“…Mann-Whitney test was used to compare the means of periodontal parameters between the www.dental.usm.my/aos/ original article | Periodontal disease in type 2 diabetic patients with dry mouth condition 81 Saliva is an important fluid in the oral cavity; one of its many functions is to clear the oral cavity of bacteria, which could potentially harm the periodontium. Many studies have shown that DM and periodontal disease are biologically linked together (Preshaw et al, 2012;Casanova et al, 2014;Molina et al, 2016). Moreover, xerostomia and salivary gland hypofunction have also been reported in DM subjects (Chávez et al, 2000;Chávez et al, 2001;Moore et al, 2001;Bajaj et al, 2012), which could be more damaging to the periodontium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mann-Whitney test was used to compare the means of periodontal parameters between the www.dental.usm.my/aos/ original article | Periodontal disease in type 2 diabetic patients with dry mouth condition 81 Saliva is an important fluid in the oral cavity; one of its many functions is to clear the oral cavity of bacteria, which could potentially harm the periodontium. Many studies have shown that DM and periodontal disease are biologically linked together (Preshaw et al, 2012;Casanova et al, 2014;Molina et al, 2016). Moreover, xerostomia and salivary gland hypofunction have also been reported in DM subjects (Chávez et al, 2000;Chávez et al, 2001;Moore et al, 2001;Bajaj et al, 2012), which could be more damaging to the periodontium.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, these collagen fibres accumulate in the tissues and thickened the basement membrane, a condition which could impair oxygen diffusion, waste elimination, leukocyte migration, and the diffusion of immune factors. These disorders would then contribute to the pathogenesis of periodontitis (Lalla et al, 1998;Molina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…5 Diabetes mellitus is considered to be one of the important factors involved in promoting the risk for the diseases of oral periodontium 15 . Molina et al, reported that almost every parameter of periodontal disease is adversely affected by diabetes 16 . In the present study, the factors like age; gender, socioeconomic status, education level and frequency of oral hygiene measures were matched between the groups (Table 1, Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Por lo explicado anteriormente, la EP se consideraría un factor de riesgo en la patogénesis de numerosas enfermedades sistémicas, incluida la DM [9][10][11][12] .…”
Section: Introductionunclassified